Pengaruh Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Kemilau Permata Sawit - Saddam Muzaki; Chintya Ones Charli; Vivi Nila Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of communication and the work environment on employee performance, with job satisfaction as an intervening variable at PT. Kemilau Permata Sawit. This study employed a quantitative approach with a survey method, distributing questionnaires to employees. The sampling technique used proportional sampling, while data analysis employed path analysis based on Partial Least Squares (PLS). The results showed that communication had a positive and significant effect on employee job satisfaction and performance. The work environment had a positive and significant effect on employee performance, but not on job satisfaction. Furthermore, job satisfaction was shown to have a positive and significant effect on employee performance. Job satisfaction, as an intervening variable, was shown to mediate the effect of communication on employee performance, but not the effect of the work environment on employee performance. This research is expected to provide management with consideration in improving employee performance through more effective communication and work environment management.